1986
DOI: 10.1002/nau.1930050103
|View full text |Cite
|
Sign up to set email alerts
|

Continuous recording of urethral activity in healthy female volunteers

Abstract: The pressure variations at the maximal urethral closure pressure (MUCP) were continuously recorded in healthy female volunteers by means of a two-point microtip transducer catheter for one hour. Before the investigation a normal voiding was assured objectively and bladder instability was excluded.All women showed pressure variations both at the MUCP and more distally. The pressure variations, from 3 to 66 cm H20, showed rhythmicity and three frequency ranges could be identified. Slow pressure waves with a freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…in the high pressure zone, and may in part account for the variation found. Finally, biological variation is also an influence as it is known that the urethral pressure shows significant spontaneous oscillations which may very well have influenced the present measurements [20,26].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…in the high pressure zone, and may in part account for the variation found. Finally, biological variation is also an influence as it is known that the urethral pressure shows significant spontaneous oscillations which may very well have influenced the present measurements [20,26].…”
Section: Discussionmentioning
confidence: 96%
“…This was partly because it would prolong the total duration of the examination unacceptably for the subjects, but also because the pressure decay which may be neglected is likely to be so slow that it is of no or minimal physiological significance. Besides, it is uncertain whether extended relaxation takes place in vivo when the normal regulation mechanisms are intact, and extended evaluations of urethral pressure in men as well as in women have shown no signs of a prolonged stress-relaxation, even though significant fluctuations in urethral pressure are evident [20,26].…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that the ''guarding'' is aberrant as there is a probable reduced urethral sphincter activity in the presence of detrusor overactivity. Loss of urethral resistance or urethral instability is a common finding in association with detrusor overactivity [19]. Wise et al [20] found a spontaneous fall in urethral pressure in 42% of patients with detrusor overactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, urethral pressure variations during filling cystometry are considered as an artefact and, therefore, of no relevance for explaining symptoms of patients by some investigators [2] . Slow-wave, rhythmic urethral pressure variations have been shown in healthy volunteers and may be an aspect of normal urethral physiology that could contribute to continence and prevention of urinary tract infection and need to be considered as pathophysiological [27] . McLennan et al [23] published on the significance of urethral pressure measurements during filling cystometry.…”
Section: Discussionmentioning
confidence: 99%